2007
DOI: 10.1542/peds.2007-2679
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Fibrillation and the Use of Automated External Defibrillators on Children

Abstract: The use of automated external defibrillators (AEDs) has been advocated in recent years as a part of the chain of survival to improve outcomes for adult cardiac arrest victims. When AEDs first entered the market, they were not tested for pediatric usage and rhythm interpretation. In addition, the presumption was that children do not experience ventricular fibrillation, so they would not benefit from use of AEDs. Recent literature has shown that children do experience ventricular fibrillation, and this rhythm ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Current guidelines recognize a knowledge gap in the lowest age and weight for safe and effective AED use, though they ultimately recommend their use in infants with apparent cardiac arrest . Hesitancy for AED use in small infants arises from a concern for myocardial damage from energy doses of adult or even pediatric‐attenuated AED pads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current guidelines recognize a knowledge gap in the lowest age and weight for safe and effective AED use, though they ultimately recommend their use in infants with apparent cardiac arrest . Hesitancy for AED use in small infants arises from a concern for myocardial damage from energy doses of adult or even pediatric‐attenuated AED pads.…”
Section: Discussionmentioning
confidence: 99%
“…Automated external defibrillators (AEDs) have been successfully used in children, but relatively little is known regarding their safety in neonates and infants . Current guidelines recognize a knowledge gap in the lowest age and weight for safe and effective use . The purpose of this case presentation is to exemplify AED use in early infancy and illustrate a rare syndrome of infant ventricular fibrillation (VF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of cardiac arrest reported ventricular fibrillation rates of 7.6% for children 1–7 years of age and 27.0% for children 8–18 years of age, with an overall incidence of ventricular fibrillation of 17.6% 2. Many guidelines, including those of the International Liaison Committee on Resuscitation, the American Heart Association (AHA), and the National Association of EMS Physicians, now advocate AED use on children to analyse rhythms and provide early defibrillation in cases of ventricular fibrillation 3 – 5…”
Section: Discussionmentioning
confidence: 99%
“…14,15 An AED program is to be covered by a school policy, 16 and staff members who are trained for such use are to be able to respond effectively to first aid and cardiopulmonary emergencies. Sudden cardiac arrest has an estimated annual incidence of 0.7 to 1.0 per 1000 population [17][18][19][20] and is responsible for Ͼ50% of all deaths attributable to cardiovascular disease in the United States.…”
Section: Policies and Procedures For Specific Emergenciesmentioning
confidence: 99%